Relationship of Physical Properties and Crystal Structure CaCO3 Purebred Chicken Egg Shells - Musfirah Cahya Fajrah; Amirah Wardah; Bambang Soegijono (Jurnal Penelitian Pendidikan IPA, 2025)
Preliminary research has been carried out on purebred chicken egg shells with research linking the physical properties and crystal structure of CaCO3 of purebred chicken egg shells. The XRF results showed the atomic elements Si, P, Ca, Ti, Fe, Zn and Sr, with a Ca content of 95.603%. The use of 3%, 5% and 10% mixing variation methods, at heating temperatures of 900oC, 1000oC, 1100oC and 1200oC. The physical properties of dry shrinkage and water absorption decreased for each mixing variation and heating temperature, while the burn shrinkage values, density, and fracture strength increased for each mixing and heating temperature. The crystal structure formed did not change the mixing variation and heating temperature, namely the result of MATCH entry number 96-901-5692 of the hexagonal crystal system, the space group R-3C and the cell units a=b= 4.9771Ǻ and c = 17.3369Ǻ.